2004
DOI: 10.1002/jhet.5570410423
|View full text |Cite
|
Sign up to set email alerts
|

Indium‐mediated facile preparation of 2‐(heterocyclic thio)‐1‐(2,3,4‐trimethoxyphenyl)ethanone in aqueous media

Abstract: An environmentally benign and efficient process for the preparation of 1‐(2,3,4‐trimethoxyphenyl)‐2‐substituted heterocyclic thio ethanone derivatives was achieved by the reactions of mercapto compounds with 2‐bromo‐1‐(2,3,4‐trimethoxyphenyl)ethanone in water mediated by indium in very high yields. Antifungal activities of the compounds were examined and moderate activity was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The infrared spectra were recorded on a Bruker VECTOR22 spectrometer in KBr disks. 1 H NMR (solvent CDCl 3 ) and 13 C NMR spectra (solvent CDCl 3 ) were performed on a Varian-INOVA 400 MHz spectrometer at room temperature using TMS as internal standard. The mass spectra were taken on an HP5988A spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The infrared spectra were recorded on a Bruker VECTOR22 spectrometer in KBr disks. 1 H NMR (solvent CDCl 3 ) and 13 C NMR spectra (solvent CDCl 3 ) were performed on a Varian-INOVA 400 MHz spectrometer at room temperature using TMS as internal standard. The mass spectra were taken on an HP5988A spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Considered that 1,3,4-thiadiazole compounds tend to contain multi-structure in a molecule, the biological activity of these compounds may be improved by the promotion of these combination with the cell's microstructure and the accumulation of various biological activities resulting from the incorporation of different heterocyclic and non-heterocyclic nucleated changes on biological activity of the compounds [6][7][8]. In our previous work in it, we reported that some 2-(1H-1, 2, 4-triazol)-1-(2,3,4-trimethoxyphenyl)ethanoxime ester derivatives showed fungicidal activities [9][10][11][12][13][14]. Based on the theory of structure-activity relationship, we modified these structures by replacement of 1,2,4-triazole with benzothiazole group and found that some of them still kept high virucidal activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,3-trimethoxybenzene (1) was prepared from pyrogallol etheration [15], substituted acetophenone (2) was prepared from trimethoxybenzene and acetic anhydride via Friedel-Crafts acetylation reaction [16], while compound 3 was synthesized by bromination of substituted acetophenone (2). The ethanone 4a was prepared by alkylation of thioles [17,18]. The reaction of compound 4 with hydroxylamine was carried out in methanol catalyzed by pyridine to produce compound 5, and the reaction was completed within 5 h at refluxing temperature [19,20].…”
Section: Chemistrymentioning
confidence: 99%
“…10 In our effort to develop a new strategy for the synthesis of thioether derivatives, we studied the one-pot indiummediated thioetherification reaction of 2-(heterocyclic thio)-1-(2,3,4-trimethoxyphenyl)ethanone in aqueous media. 11 In this paper, we would like to report a new green method for synthesizing the title compound with indium trichloride used as catalyst to promote the formation of thioether derivatives containing 1,2,4-triazole moiety at room temperature in aqueous media. This method was easily in process, mild in condition, environmentally friendly and high yielding.…”
Section: Introductionmentioning
confidence: 99%